Karakteristik Kimiawi Kompos Enceng Gondok dan Jerami Hasil Dekomposisi Dengan Aktivator Alami dan Buatan - Nike Triwahyuningsih (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
A research to study the chemical properties of hyacinth- and straw-compost decomposed by natural and artificial activators was conducted at the Research Field of Faculty of Agriculture, Muhammadiyah University of Yogyakarta. Cow manure was used as natural activator, while Stardec (powdered) and EM4 (liquid) as artificial ones. The treatment was arranged in 2x3 factorial completely randomized design. The hyacinth and straw organic sources were decomposed by cow manure, Stardec and EM4 activators. Organic matters were incubated for 5-6 weeks then pH, C-organic, N-total, available P and K, CEC, and the .exchngeable  Ca,  K and Mg were measured. The results showed that the hyacinth-compost had the better maturity according to the C/N ratio (C/N20) than the straw-compost (C/N20), but the two kinds of compost had the moderate mature rate of humic substances.  The straw-compost had better quality though as shown in its higher available phosphorus and excheangable potassium, especially when decomposed by EM4 artificial activator. Application of artificial activators Stardec and EM4 enhanced the maturity rate of hyacinth-compost.